Neuregulin1 ameliorates metabolic dysfunction-associated fatty liver disease via the ERK/SIRT1 signaling pathways - Chengan Xu; Shouhao Wang; Di Meng; Mingshan Wang; Rong Yan; Yining Dai (BMC Gastroenterology)
Abstract Background Neuregulin (NRG) family is involved in energy metabolism, among which NRG1 is a neuregulin proved to play a protective role in MAFLD cells. But the presice echanism has not been fully illustrated. This study aimed to investigate the role of NRG1 via the ERK/SIRT1 signaling in the pathogenesis of MAFLD. Methods C57BL/6 mice were fed with high-fat diet for 8 weeks, and then injected with NRG1 (0.3 mg/kg/d) and PD98059 (0.3 mg/kg/d) via tail vein for 5 weeks. HepG2 cells induced by oleic acid and palmitic acid were treated with 20ng/mL NRG1 and 10µmol/L PD98059. The changes of histopathological, biochemical indexes, inflammatory factors, lipid metabolism, apoptosis and autophagy parameters were measured. Results The expressions of NRG1 in MAFLD cell and animal models were significantly lower than that in the control group. After the intervention of ERK inhibitor PD98059, the expression of NRG1 decreased significantly in vivo, but no significant change was observed in vitro. Moreover, NRG1 ameliorated hepatic steatosis, enhanced cell viability, reduced cell apoptosis, and attenuated liver injury both in vitro and in vivo. After NRG1 intervention, the expressions of ERBB2, ERBB3, p-ERK1/2, SIRT1 and p-FOXO1 as well as the LC3II/I ratio in MAFLD cells and liver tissues of MAFLD mice were significantly increased, while the expression of SREBP1c was decreased. The aforementioned therapeutic effect of NRG1 was lost after the intervention of PD98059. Conclusion NRG1 might play a protective role in the pathogenesis of MAFLD by activating the downstream ERK1/2 through ErbB2-ErbB3, which promotes the expression of SIRT1 and autophagy markers. This study might indicate a new therapeutic strategy for MAFLD.